2014
DOI: 10.1139/cjp-2013-0389
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and ionization of the hydrogen atom by intense femtosecond chirped laser pulses

Abstract: The excitation and ionization processes of the hydrogen atom by intense femtosecond chirped laser pulses are investigated by solving numerically the three-dimensional time-dependent Schrödinger equation. We study, in three distinct cases, the interaction of the atomic system with chirped pulses of different central carrier frequencies that correspond to some harmonics of a Ti–sapphire laser. We analyze, in each case, the mechanism of the population transfer from the ground to the excited electronic states and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…( 4), (5), and (7) does not depend on the chirp, i.e., all the spectrum profiles of the chirped pulses remain the same as the tranform-limited case. We notice that in the recent study, [53] the definition of the chirped pulses does not make sure the spectrum profile is independent on the chirp, though in a related work about H atom [57] by the same authors exactly the same definition for the chirped pulses with the present work is taken. It is in fact our initial motivation to see how a more physical definition for the chirp pulse will influence the conclusion of Ref.…”
Section: Theoretical Methodsmentioning
confidence: 85%
“…( 4), (5), and (7) does not depend on the chirp, i.e., all the spectrum profiles of the chirped pulses remain the same as the tranform-limited case. We notice that in the recent study, [53] the definition of the chirped pulses does not make sure the spectrum profile is independent on the chirp, though in a related work about H atom [57] by the same authors exactly the same definition for the chirped pulses with the present work is taken. It is in fact our initial motivation to see how a more physical definition for the chirp pulse will influence the conclusion of Ref.…”
Section: Theoretical Methodsmentioning
confidence: 85%
“…There are many different types of chirped pulses used in the experimental and theoretical studies, and those chirped laser pulse can be categorized into linear [28][29][30][31][32][33][34] and nonlinear chirped pulse. [35,36] Especially, two different expressions of the linear chirped pulse with Gaussian shape have been given by Tong et al [29] and Barmaki et al, [30] which have been used by experimental and theoretical physicists respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Nakajima et al [17] investigated the ATI of Na by chirped infrared laser pulses by solving the three-dimensional time-dependent Schrödinger equation (3D-TDSE) and attributed the chirp dependence of the photoelectron angular distributions (PADs) to the excited bound states in the multiphoton ionization processes. Laulan et al [18] studied excitation and ionization of hydrogen atoms in intense chirped laser pulses. Xiang et al [19] found that the cutoff of the ATI of one-dimensional H atoms can be extended dramatically using a few-cycle nonlinear chirped laser pulse.…”
Section: Introductionmentioning
confidence: 99%